2015
DOI: 10.1177/0956797615609578
|View full text |Cite
|
Sign up to set email alerts
|

What Comes After /f/? Prediction in Speech Derives From Data-Explanatory Processes

Abstract: Speech perception is a difficult problem most listeners solve effortlessly. Acoustic cues are short-lived and highly variable. Here we demonstrate that part of the solution is predictions modulated by high-level expectations. Listeners heard isolated fricatives (e.g., “s”, “sh”) and predicted the upcoming vowel. Accuracy was above chance, suggesting fine-grained detail in the signal can be used for prediction. A second group performed the same task but saw a still face and a letter corresponding to the fricati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…For example, a stimulus with a VOT of 20 ms could be a /b/ in slow speech or a /p/ in fast speech. Despite over 40 years of research, speech scientists have identified few (if any) acoustic cues that unambiguously identify a phoneme across different contexts (e.g., McMurray & Jongman, 2015; Ohala, 1996). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a stimulus with a VOT of 20 ms could be a /b/ in slow speech or a /p/ in fast speech. Despite over 40 years of research, speech scientists have identified few (if any) acoustic cues that unambiguously identify a phoneme across different contexts (e.g., McMurray & Jongman, 2015; Ohala, 1996). …”
Section: Introductionmentioning
confidence: 99%
“…Such processes may underlie the well-known trading relations that have been documented in speech perception (Repp, 1982; Summerfield & Haggard, 1977; Winn, Chatterjee, & Idsardi, 2013). This kind of combinatory process would also be necessary for accurately compensating for higher level contextual expectations—for example, recoding pitch relative to the talker’s mean pitch (McMurray & Jongman, 2011, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical predictive frameworks have been recently extended to explain phenomena in language processing (Farmer et al, 2013;Kuperberg & Jaeger, 2016;McMurray & Jongman, 2016). According to these frameworks, expectations at higher levels of processing (e.g., syntactic) create hypotheses and send those to lower levels of representation (e.g., word recognition).…”
Section: Predictive Processing In Languagementioning
confidence: 99%
“…First, processes like coarticulation and assimilation leave fine-grained, subcategorical traces in the signal (e.g., Gow, 2001), which can be used to anticipate upcoming speech sounds speeding up processing. Multiple studies suggest that listeners take advantage of anticipatory coarticulatory information in this way (Gow, 2001;Mahr, McMillan, Saffran, Ellis Weismer, & Edwards, 2015;McMurray & Jongman, 2015;Salverda, Kleinschmidt, & Tanenhaus, 2014;Yeni-Komshian, 1981). However, as these modifications are largely within-category, such anticipation is only possible if listeners are sensitive to this fine-grained detail.…”
Section: The Functional Role Of Gradiencymentioning
confidence: 99%
“…For example, a stimulus with a voice onset time (VOT) of 20 ms could be a /b/ in slow speech or a /p/ in fast speech. In fact, despite over 40 years of research, phoneticians and speech scientists have identified few (if any) acoustic cues that unambiguously identify a phoneme across different contexts (e.g., McMurray & Jongman, 2015;Ohala, 1996).…”
mentioning
confidence: 99%